Association of Measured Quality and Future Financial Performance Among Hospitals Performing Cardiac Surgery. Issue 5 (September 2022) - Enumah, Samuel J.; Sundt, Thoralf M.; Chang, David C.
Abstract : Goal: For decades, hospitals performing cardiac surgery have carried the cost of implementing quality improvement activities and reporting quality outcomes. However, the financial return of such investments is unclear, which weakens the incentive for hospitals to invest in quality improvement activities. This study explored the relationship between a hospital's measured quality and its financial performance. Methods: Using data from the American Hospital Association and Hospital Compare from 2014 to 2018, we performed an observational study of hospitals performing cardiac surgery. We used mixed-effects regression models with fixed-year effects and random intercepts to explore associations between measured quality and hospital financial performance. Our dependent variables were margins (profit divided by revenue) and financial distress; our independent variables included Patient Safety Indicator 90 (PSI-90) and hospital characteristics. Principal Findings: Our sample included 4, 927 hospital-years from 1, 209 unique hospitals. Hospitals in the worst-performing PSI-90 score quartile experienced a lower operating margin (−1.26%, 95% CI [−2.10 to −0.41], p = .004), a lower total margin (−0.92%, 95% CI [−1.66 to −0.17], p = .016), and an increased odds of financial distress in the next year (OR: 2.12, 95% CI [1.36–3.30], p = .001) when compared with the best-performing hospitals. Practical Applications: Our exploration into financial distress provides managers with a better understanding of the relationship between a hospital's measured quality and its financial position. In reflecting on our findings, hospital leaders may consider viewing patient safety as a modifiable factor that can improve their organization's overall financial health. Our findings suggest that excellent safety performance may be both financially and clinically beneficial to hospitals.